Ethnobotany: From the Traditional to Ethnopharmacology - Martinez-Salinas, J (CRC Press, 2023)
In this book we present recent studies that have been carried out on some widely used medicinal plants. The need for new and alternative treatments stem from the lack of efficiency of existing remedies for certain illnesses. We have compiled information that may be useful to researchers in their quest to develop new drugs. © 2023 Taylor and Francis Group, LLC.